EXPLORING PHONOLOGY AND SIGN LANGUAGE AS CATALYSTS IN MODERN COMMUNICATION - Jakhar, Dr. Monika (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
Phonology, focusing on the sounds of spoken language, forms the bedrock of oral communication and intertwines with technology, while sign language, a visual-gestural medium, champions inclusivity for the Deaf community. This symbiotic relationship not only enhances our understanding of linguistic diversity but also shapes a more interconnected and inclusive global dialogue, breaking down barriers and fostering a dynamic and enriched communication landscape. The articulators of sign language are the visible and moveable portions of the body, including the hands, face, head, and upper torso. These articulators are responsible for conveying prosody, as well as for shaping, restricting, and contrasting words. An introduction to the structure of phonology in the non-verbal language of sign language is given in this article.